Technopreneurship and IT-preneurship in vocational education perspective: Perspective theory - Sakti, Rizki Hardian; Yetti, Wirda; Wulansari, Risky Ema (Universitas Negeri Padang, 2020)
This study aimed to examine a descriptive review of technopreneurship and IT-preneurship viewed from an aspect of vocational education perspective. Descriptively, this research will provide an overview of the technopreneurship and IT-preneurship that must be possessed by vocational tertiary institutions. Technopreneurship and IT-preneurship is one part of entrepreneurship based on technology. The world of vocational education is obliged to produce generations who not only have an entrepreneurial spirit, but also have a spirit of technopreneurship and IT-preneurship. Communicating important technology in developing entrepreneurial spirit is a challenge for the world of vocational education. This article is a conceptual paper related to publish publications related to the themes in this article and this article discusses the concepts of technopreneurship and IT preneurship in the perspective of vocational education and also enhances entrepreneurship development in the world of vocational education.